2007
DOI: 10.1188/07.onf.359-364
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Modality Use and Beliefs Among African American Prostate Cancer Survivors

Abstract: Purpose/Objectives-To examine the cultural beliefs and attitudes of African American prostate cancer survivors regarding the use of complementary and alternative medicine (CAM) modalities.Research Approach-Mixed methods with primary emphasis on a phenomenology approach. Setting-In-person interviews in participants' homes and rural community facilities.Participants-14 African American men diagnosed with and treated for prostate cancer.Methodologic Approach-Personal interviews using a semistructured interview gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 17 publications
3
52
0
Order By: Relevance
“…Hispanic and black men were significantly more likely to report mind-body medicine use with or without prayer. A prior study suggested that prayer is a highly valued CAM modality among African American prostate cancer survivors as a way to cope with their disease [33]. Patients being cared for by Kaiser Permanente in Northern California were significantly more likely to report biologically based CAM use.…”
Section: Discussionmentioning
confidence: 94%
“…Hispanic and black men were significantly more likely to report mind-body medicine use with or without prayer. A prior study suggested that prayer is a highly valued CAM modality among African American prostate cancer survivors as a way to cope with their disease [33]. Patients being cared for by Kaiser Permanente in Northern California were significantly more likely to report biologically based CAM use.…”
Section: Discussionmentioning
confidence: 94%
“…36,40,43,45,47 Spirituality was cited repeatedly as both a coping mechanism and a factor in the decision-making process. Spirituality was a particularly strong coping mechanism among African Americans.…”
Section: Resultsmentioning
confidence: 99%
“…Spirituality was a particularly strong coping mechanism among African Americans. 40,45 Specifically, spirituality played a strong role in having faith in the providers, strengthening the relationship with providers, and following the providers’ recommendations for treatment. In these studies, prayer was not viewed as a sufficient treatment option by itself.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In addition, the integration of CAM services into health care systems and the improved regulation of practitioners and practices encourage patients with cancer to participate in such services as part of their cancer care. 3,8 However, the willingness of patients with cancer to practice CAM therapies can also be related to more personal and subjective reasons, such as their health beliefs, [9][10][11][12] their beliefs regarding the risks and benefits of CAM use 8,11,[13][14][15][16][17] as well as the conventional treatment, 3,8,14,18 and their past experiences. 3,8 Personal and subjective parameters may also influence patients' posttreatment satisfaction and perceived effectiveness, and these are unnecessarily related to objective scales and outcomes.…”
Section: Introductionmentioning
confidence: 97%